The Combinational Effect of Enhanced Infection Control Measures and Targeted Clinical Metagenomics Surveillance on the Burden of Endemic Carbapenem and Other β-Lactam Resistance Among Severely Ill Pediatric Patients - Athina Giampani; Maria Simitsopoulou; Maria Sdougka; Christos Paschaloudis; Emmanuel Roilides; Elias Iosifidis (Biomedicines)
Background: Antimicrobial resistance (AMR) is recognized as one of the most important global public health threats. There is an urgent need to reduce the spread of these multidrug-resistant bacteria (MDR-B), particularly in extremely vulnerable patients. The aim of this study was to investigate whether targeted gene amplification performed directly on clinical samples can be used simultaneously with a bundle of enhanced infection control measures in a Pediatric Intensive Care Unit (PICU) endemic to MDR-B. Methods: This study had three phases: (1) the baseline phase was performed prior to intervention when first screening and sample collection were performed; (2) the intervention phase was performed when various enhanced infection control measures (EICM) were applied; and (3) the maintenance phase occurred when EICMs were combined with the implementation of targeted molecular surveillance. The presence of four carbapenemase genes, blaKPC, blaOXA-48-like, blaVIM, and blaNDM, as well as the β-lactamase genes blaTEM and blaSHV, was evaluated by PCR after DNA isolation directly from stool samples. The results were compared to culture-based phenotypic analysis. Results and Conclusions: The implementation of EICM appeared to reduce the resistance burden in this sample endemic to an MDR-B clinical setting. The direct implementation of a targeted and customized rapid molecular detection assay to clinical samples seems to be an effective clinical tool for the evaluation of EICM measures.